FMPOD: A Novel Focus Metric Based on Polynomial Decomposition for Infrared Microscopy - Raphael Abele; Redouane El Moubtahij; Daniele Fronte; Pierre-Yvan Liardet; Jean-Luc Damoiseaux; Jean-Marc Boi; Djamal Merad (IEEE Photonics Journal, 2019)
This paper proposes an innovative autofocus method to ensure the image of an integrated circuit is correctly in focus under an infrared microscope. It discusses the difficulties inherent to the optical system and explores several inefficient methods used for natural scenes. It will also present a Focus Metric based on POlynomial Decomposition (FMPOD) adapted to our context. This approach relies on analyzing the projection of images on an orthonormal polynomial basis. Its robustness is tested using different magnifying lenses in addition to multiple distortions. In conclusion, we will demonstrate how this novel approach outperforms existing methods related to our work environment.